Kadın konulu Türk-Rus atasözleri üzerine toplum dilbilimsel bir inceleme - Zaraeva, Ekaterina (My University, 2018)
Atasözlerinin dili zenginleştiren en önemli unsurlardan biri olduğu, herhangi bir ispata gerek duymayan bir gerçektir. Sosyal bir toplumdaki bazı hayat görüşleri ise az ya da çok atasözlerine dayanmaktadır. Günümüzde aktüel bir sorun olan Rus ve Türk toplumundaki kadının yerinin, söz konusu atasözlerindeki kadın imajı ile karşılaştırılması bu çalışmanın konusunu oluşturmaktadır.

Proverbs are one of the most important elements enriching the language, a fact that does not require any proof. Some points of view of the life in social society are more or less based on proverbs. The current issue of comparing the woman’s place in the Russian and Turkish societies, which is a real problem, with the image of the woman passing in the proverb, constitutes the subject of this study.
Keywords: Atasözleri, Türk; female image; feminism; feminizm; gender; kadın imajı; kadının sosyal konumu; Kadınlar, Edebiyatta; Kelimeler ve cümleler; Proverbs, Turkish; social status of women; Terms and phrases; toplumsal cinsiyet; turkish and russian proverbs; Turkish language; Türk dili; türk ve rus atasözleri; Women in literature